2018
DOI: 10.1007/s40136-018-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Biofilms and Superantigens in Chronic Rhinosinusitis

Abstract: Purpose of review: This review explores recent discoveries in our understanding of how biofilms and superantigens contribute to the pathogenesis of chronic rhinosinusitis (CRS). It also examines clinical implications and novel treatment approaches for biofilm associated CRS. Recent findings: While the role of biofilms in CRS has been studied for 14 years, research interest has now turned toward elucidating new methods of biofilm detection, microbial diversity, and novel treatment approaches. Recent studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 97 publications
0
34
0
2
Order By: Relevance
“…The presence of biofilm has been associated with worse pre-operative radiological scores and post-operative outcome, as well as higher risk of recurrence [163][164][165][166]. S. aureus biofilm in particular appears to be more pathogenic than other bacterial species, and this has been suggested to be due to a severe local inflammatory response to S. aureus superantigens [167].…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 99%
“…The presence of biofilm has been associated with worse pre-operative radiological scores and post-operative outcome, as well as higher risk of recurrence [163][164][165][166]. S. aureus biofilm in particular appears to be more pathogenic than other bacterial species, and this has been suggested to be due to a severe local inflammatory response to S. aureus superantigens [167].…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 99%
“…Bacterial biolms appear to be involved in various respiratory tract infections including various pulmonary infections, as well as upper respiratory tract infections such as chronic rhinosinusitis, adenoiditis, chronic and recurrent middle ear infection, and recurrent tonsilitis. 7,87,88 P. aeruginosa biolms infections are the leading cause of morbidity and mortality in cystic brosis (CF) patients. 7,89 Chronic rhinosinusitis leads to 4.1 million physician visits annually and is oen treated surgically.…”
Section: Murine Cutaneous Abscess Infection Modelmentioning
confidence: 99%
“…Multidrug-resistant bacteria and polymicrobial biofilms are still a major challenge [ 33 ]. Topical antibiotic agents are a research hotspot recently because they can provide higher concentrations of antibiotics locally and limited systemic absorption [ 34 ]. A previous study compared nebulized antibiotics to nebulized saline; although CRS symptoms were found to be improved, nebulized antibiotics failed to offer additional benefits when compared with saline [ 35 ].…”
Section: Compoundsmentioning
confidence: 99%